Photochemische Umwandlung und Speicherung von Sonnenenergie - Ernst Schumacher (CHIMIA)
A world-wide renaissance of interest in photochemical processes with visible light is gaining momentum. It is stimulated by the prospects of achieving storage of solar energy in chemical compounds whose usable energy density, life-time and economics is by far superior to storage of heat. A realistic maximum storage efficiency of the total incident radiation power of ≲ 16% can be expected. This is about 20 to 100 times better than the production of wood or cane-sugar per equally irradiated surface. However, the processes to be designed, must meet stringent economical boundary conditions because of the small average power density of the sun’s radiation. Only a sophisticated solution will be acceptable. The present status and future activities in this field are discussed.